2017
DOI: 10.1007/s13197-017-2920-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of malt process steps on bioactive properties and fatty acid composition of barley, green malt and malt grains

Abstract: In this study, the effect of barley malt process on antioxidant activity, carotenoid content, oil yield, phenolic compounds and fatty acid composition of barley, green malt and malt was investigated. The highest antioxidant activity (79.80%) and total phenolic content (122.43 mg/100 g) was observed in green malt. Carotenoid content of green malt (1.71 µg/g) was higher than those of barley and malt. Green malt had the maximum (+)-catechin (69.06 mg/100 g), 1,2-dihydroxybenzene (37.21 mg/100 g), quercetin (30.78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
4
13
0
Order By: Relevance
“…Moreover, barley, malt, and Brazilian peanut oils also presented high contents of fatty acids, especially LA (51.7%, 56.6%, and 44.4–48.2%, respectively). The contents of these decreased during the malting process (Özcan, Juhaimi, & Uslu, ; Özcan, Juhaimi, & Uslu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, barley, malt, and Brazilian peanut oils also presented high contents of fatty acids, especially LA (51.7%, 56.6%, and 44.4–48.2%, respectively). The contents of these decreased during the malting process (Özcan, Juhaimi, & Uslu, ; Özcan, Juhaimi, & Uslu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, [73] showed that the total lipid content and fatty acid composition varies with the barley variety and decreases during the malting process. However, a study showed that barley lipids contained 18.53% palmitic, 19.94% oleic and 51.74% linoleic acids while malt oil contained 17.33% palmitic, 15.62% oleic and 56.56% linoleic acids, and linoleic acid content increased during the malting process while oleic and palmitic acid content decreased [64].…”
Section: Phenolic Acidsmentioning
confidence: 98%
“…Out of major proanthocyanidins in barley, prodelphinidin B3 (90-197 μg/g) accounted for the majority of proanthocyanidins, whereas procyanidin C2 (5-19 μg/g) was reported to be present only in minor quantities [63]. In the malting process, the green malt had the highest antioxidant activity (79.80%) and total phenolic content (122.43 mg/100 g) than those of barley and malt [64]. For example, carotenoid (1.71 μg/g), (+)-catechin (69.06 mg/100 g), 1,2-dihydroxybenzene (37.21 mg/100 g), quercetin (30.78 mg/100 g) and isorhamnetin (22.44 mg/100 g) contents were higher in green malt.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…flavan-3-ols, phenolic acids and ferulic acid, which are delivered to the brewing process (1,82). The antioxidant properties of barley and malt are mostly associated with phenolic compounds such as phenolic acids, flavonoids, proanthocyanidins and tannins (85,86), as well as some of the Maillard reaction products (MRPs), in particular, melanoidins and reductones (87). Phenolic compounds that are ultimately found in beer originate to a large extent from malt (e.g.…”
Section: -Methylpropanalmentioning
confidence: 99%